Less Is Not More: Information Presentation Complexity and 401(k) Planning Choices - Eric Cardella; Charlene M. Kalenkoski; Michael Parent (Institute of Labor Economics (IZA), 2018)
This paper presents the results of an experiment that is designed to examine how information presentation and complexity impact retirement-savings behavior. The experiment is performed twice, using both a Qualtrics panel of new employees and a sample of business school students. In this experiment, participants first were provided with either a long or short description of a hypothetical employer-sponsored 401(k) plan. Then they were asked whether they would enroll in the hypothetical plan and, if so, what percentage of their salary they would contribute. If they chose to contribute, they were asked how they would like to allocate their contribution between stocks and bonds. Participants were offered the option to stick with pre-assigned default options such as a 4% contribution and a 50-50 stocks and bonds split. The hypothesis is that providing concise information with helpful recommendations would improve choices over providing lengthy and detailed information. However, controlling for demographic and other factors, this hypothesis was not supported by the data, for either the new employees or the business school students. Thus, the data suggest that simplifying the presentation of retirement-plan information to employees is unlikely to result in vastly improved retirement-planning choices.
Keywords: G11; G41; H31; J32; D83; C90; 330; retirement planning; 401(k); information complexity; nudge; choice architecture